2013
DOI: 10.1248/bpb.b12-00702
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Inhibitor of Stearoyl-CoA Desaturase-1 Attenuates Hepatic Lipid Accumulation, Liver Injury and Inflammation in Model of Nonalcoholic Steatohepatitis

Abstract: Stearoyl-CoA desaturase-1 (SCD-1) catalyzes the biosynthesis of monounsaturated fatty acids, and their abnormality is possibly responsible for obesity, insulin resistance, hepatic steatosis and nonalcoholic steatohepatitis (NASH). A novel SCD-1 inhibitor, N-(2-hydroxy-2-phenylethyl)-6-[4-(2-methyl benzoyl) piperi din-1-yl]pyridazine-3-carboxamide, has been obtained. The compound inhibited liver SCD-1 activity and increased liver triglyceride accumulation in mice fed with non-fat, high-sucrose diets. In order t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
19
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 46 publications
3
19
0
Order By: Relevance
“…It can be therefore expected that the effect of fenofibrate on ScdI is mediated by PPARα activation. It has been demonstrated in a rat model of non-alcoholic steatohepatitis (NASH) (rats fed a methionine and choline-deficient diet) that pharmacological inhibition of Scd1 is associated with reduced hepatic steatosis, lower ALT and AST levels, and amelioration of hepatocellular degeneration and inflammation (Kurikawa et al 2013). These findings are in agreement with the results of the current study, where increased expression of Scd1 was associated with hepatotoxic effects.…”
Section: Discussionsupporting
confidence: 92%
“…It can be therefore expected that the effect of fenofibrate on ScdI is mediated by PPARα activation. It has been demonstrated in a rat model of non-alcoholic steatohepatitis (NASH) (rats fed a methionine and choline-deficient diet) that pharmacological inhibition of Scd1 is associated with reduced hepatic steatosis, lower ALT and AST levels, and amelioration of hepatocellular degeneration and inflammation (Kurikawa et al 2013). These findings are in agreement with the results of the current study, where increased expression of Scd1 was associated with hepatotoxic effects.…”
Section: Discussionsupporting
confidence: 92%
“…Hepatic activity of the lipogenic enzyme SCD-1 may be elevated in steatosis (26). Also, SCD-1-deficient mice were protected against hepatic lipogenesis, whereas SCD-1 inhibitors markedly reduced hepatic triglyceride accumulation (35). In humans, a strong association between the change in liver fat and the change in hepatic SCD-1 index was reported in weight-stable subjects (22), a finding currently confirmed during hypercaloric conditions.…”
Section: Discussionmentioning
confidence: 81%
“…In humans with NAFLD, free fatty acids, which undergo esterification into triglycerides, circulate at higher levels in the blood, leading to fat accumulation in the liver 8 9 . Another report has demonstrated that stearoyl-CoA desaturase (SCD1), an enzyme that synthesizes monounsaturated fatty acids from saturated fatty acids, plays an important role in hepatic lipid accumulation and NASH progression 10 . Moreover, depletion of the palmitate elongase, Elovl6, attenuated NASH progression in mice, and expression of Elovl6 was positively correlated with severity of steatosis and liver injury in human NASH patients 11 .…”
mentioning
confidence: 99%